Exploring the Pathway from Workplace Spirituality and Ethical Climate to Turnover Intention: The Mediating Role of Organizational Commitment - Alifa Rizqia Rachmawati (Management Analysis Journal, 2024)
This study investigates the influence of workplace spirituality and ethical climate on organizational commitment and turnover intention among inpatient nurses. Using a quantitative approach, data were collected from 165 nurses with a minimum of one year of service and analyzed through Structural Equation Modeling (SEM) done by AMOS software. The results indicate that both workplace spirituality and ethical climate have a significant positive effect on organizational commitment, and a significant negative effect on turnover intention. Additionally, organizational commitment is found to negatively influence turnover intention. The study also reveals that organizational commitment significantly mediates the relationship between workplace spirituality and turnover intention, but does not significantly mediate the relationship between ethical climate and turnover intention. These findings emphasize the importance of fostering a spiritually supportive and ethically sound work environment to enhance nurse retention and organizational commitment.